MIGRASI SIARAN TELEVISI ANALOG KE DIGITAL: ARAH FORMULASI KEBIJAKAN KOMUNIKASI REVISI UNDANG-UNDANG TENTANG PENYIARAN - Frendy Christianto Imanuel Siahaan; Guntur F Prisanto; Niken F Ernungtyas; Irwansyah Irwansyah; Syahrul Hidayanto (Jurnal Ranah Komunikasi, 2020)
This research aims to describe the direction of communication policy formulation of the Revision of the Broadcasting Law related to analog to digital broadcast migration. The research approach chosen was qualitative with the method of data collection in the form of interviews and literature studies. Based on the criteria for the formulation of communication policy, it can be interpreted that the Revision of the Broadcasting Law related to the migration of analog to digital broadcasts contains: (1) Global politics and ITU agreements as a policy context, (2) Modern broadcasting technology and the global economy as a policy domain and (3) Frequency efficiency, guaranteeing public rights in broadcasting, and improving the quality of television broadcasting as a communication policy paradigm.